Stature estimation study based on pelvic and sacral morphometric among Malaysian population - Lai, Poh Soon (2023)
This study showed that the auricular lengths, ilium dimension and acetabulum were the most useful stature estimator at R > 0.5. The combination of pelvic parameters, sacral parameters and indexes had contributed to a higher R2 value of the regression models.